Lessons for communication strategies during health emergencies from a COVID-19 knowledge, attitudes and practices study in an informal settlement in Mumbai, India - Supriya Krishnan; Jennifer Spencer; Apurva Tiwari; Sushmita Das; Anagha Waingankar; Sushma Shende; Shanti Pantvaidya; Vanessa D’souza; Armida Fernandez; Anuja Jayaraman (Discover Public Health)
Abstract The COVID-19 pandemic provided lessons for health policies across the globe. We assessed the knowledge, attitudes and practices of vulnerable populations in an informal settlement in Mumbai, India, during the pandemic. We discuss the viability and effectiveness of communication strategies based on these results and offer suggestions for policy modifications regarding awareness generation and behavioral change during health emergencies. The study was conducted through a telephone survey among 460 respondents (233 men and 226 women) from April to May 2021. Television (94%) and family (70%) were the most common sources of information, but they were not the most trusted. Most respondents were aware of the causes and preventive measures of COVID-19, including vaccination. However, this awareness did not always result in changes in attitudes and behavior- 66% perceived low or no risk to COVID-19, while 93% did not consider it essential to wear masks in workspaces and 78% did not sanitize their hands before entering workspaces. More respondents were concerned about loss of employment (53%) than about their physical (10%) or mental (4%) health. The study highlights the need for context-specific communication strategies for vulnerable populations. This includes providing reliable and accessible sources of information, emphasizing accuracy and detail, and adopting a holistic and multidimensional approach to awareness and information sharing.